Business Coaching Bagi Calon Karyawan Gerai Ikatan Pesantren Indonesia di Wilayah Provinsi Jawa Timur - Hermansyah, Muhammad (Yayasan Pusat Kemanusiaan dan Transformasi Sosial, 2023)
The Indonesian Islamic Boarding Association encourages pesantren to address the problems they face on their own, rather than relying on government assistance that has not been able to attend for pesantren. So that through empowerment programs, Islamic boarding schools must be empowered, including through the IPI Outlet For Islamic Boarding Schools, which is one part of the program implemented in accordance with the 2020 IPI National Conference Amanah, namely through the Pesantren Economic Movement, including printing young students through the IPI Outlet. In carrying out this activity, first, preparing employees through business coaching, PT. SEB will establish marketing staff in 4 districts as a pilot project for marketing staff who can gain complete knowledge about the world of Islamic boarding schools, business and entrepreneurship, as well as SOPs from IPI outlets. Increasing the potential of Islamic boarding schools in the fields of agriculture, animal husbandry, fisheries and their processed products, which will later be sold to consumers and the wider community. On the other hand, it is hoped that pesantren will have no difficulty in obtaining daily necessities through IPI outlets.